Molecular Characterization of Mg-Chelatase CHLI Subunit in Pea (Pisum sativum L.) - Wu, Cai-jun; Wang, Jie; Zhu, Jun; Ren, Jing; Yang, You-xin; Luo, Tao; Xu, Lu-xi; Zhou, Qing-hong; Xiao, Xu-feng; Zhou, Yu-xin; Luo, Sha (Frontiers in Plant Science, 2022)
As a rate-limiting enzyme for chlorophyll biosynthesis, Mg-chelatase is a promising target for improving photosynthetic efficiency. It consists of CHLH, CHLD and CHLI subunits. In pea (Pisum sativum L.), two putative CHLI genes (PsCHLI1 and PsCHLI2) were revealed recently by the whole genome sequencing, but their molecular features are not fully characterized. In this study, PsCHLI1 and PsCHLI2 cDNAs were identified by PCR-based cloning and sequencing. Phylogenetic analysis showed that PsCHLIs were derived from an ancient duplication in legumes. Both PsCHLIs were more highly expressed in leaves than in other organs and downregulated by abscisic acid and heat treatments, while PsCHLI1 was more highly expressed than PsCHLI2. PsCHLI1 and PsCHLI2 encode 422- and 417-amino acid proteins, respectively, which shared 82% amino acid identity and were located in chloroplasts. Plants with a silenced PsCHLI1 closely resembled PsCHLI1 and PsCHLI2 double-silenced plants, as both exhibited yellow leaves with barely detectable Mg-chelatase activity and chlorophyll content. Furthermore, plants with a silenced PsCHLI2 showed no obvious phenotype. In addition, the N-terminal fragment of PsCHLI1 (PsCHLI1N, Val63-Cys191) and the middle fragment of PsCHLI1 (PsCHLI1M, Gly192-Ser336) mediated the formation of homodimers and the interaction with CHLD, respectively, while active PsCHLI1 was only achieved by combining PsCHLI1N, PsCHLI1M, and the C-terminal fragment of PsCHLI1 (Ser337-Ser422). Taken together, PsCHLI1 is the key CHLI subunit, and its peptide fragments are essential for maintaining Mg-chelatase activity, which can be used to improve photosynthetic efficiency by manipulating Mg-chelatase in pea.